Development and Evaluation of Fast‑Dissolving Oral Film of Poorly Water-Soluble Drug Felodipine - Sharma, Pravin Kumar (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The objective of the presented research work was to develop and evaluate fast-dissolving oral film containing solid dispersion of Felodipine (FnFDFs) for improvement of its water solubility, dissolution, and oral bioavailability by avoiding the first pass metabolism, providing faster onset of action and avoidance of problem of dysphasia. Materials and Methods: First, solid dispersion (SDP) of Felodipine was prepared using solvent evaporation method using PVP-K30 as hydrophilic polymeric carrier in different proportions. FnFDFs were prepared using solvent casting method and optimized using Box–Behnken design by applying design-expert. The concentration of HPMC-E5 (40–45% w/w) as a film forming polymer, propylene glycol (10–15% w/w of polymer) as a plasticizer, and croscarmellose (1–5% w/w) as disintegrating agent was selected as independent variables and tensile strength, disintegration time and percentage drug dissolution was selected as a response variables. Further, FnFDFs were evaluated based on uniformity of mass, thickness, percentage drug content, folding endurance, surface pH, moisture uptake, percentage swelling, percentage elongation, tensile strength, in vitro disintegration time, in vitro percentage drug dissolution or release study, stability study, surface morphology using scanning electron microscope, ex vivo permeation study, and in vivo pharmacokinetic study. Results and Discussions: Fourier transform infrared and differential scanning calorimetry analysis revealed the compatibility between drug and excipients. Results of evaluation of FnFDFs suggested satisfactory performance for all the parameters. FnFDFs indicated in vitro disintegration time of 22.84 ± 0.31 s and in vitro percentage drug dissolution of 97.09 ± 1.54% up to 10 min, thus suggested faster drug dissolution. Moreover, in vivo pharmacokinetic study in rats revealed faster absorption and around 90% of oral bioavailability up to 1–2 h for FnFDFs through the buccal administration in comparison with that slow absorption and around 20% of oral bioavailability up to 3 h for oral suspension of Felodipine through gastrointestinal tract. Conclusion: Based on the results, it was concluded that fast-dissolving oral film contained SDP of drug may provide the merits of faster onset of action, avoidance of extensive first-pass metabolism, enhanced bioavailability, and improved patient compliance for the delivery of poorly water-soluble drug such as Felodipine.